Accumulating and Decreasing Profiles of Aldrin and its Epoxide, Dieldrin, in Hen’s Egg Yolk - N. FURUSAWA (Chemistry and Biochemistry: Research Progress Vol. 4, 2025)
This chapter presents the kinetic profiles of aldrin (AD) and its epoxide (= dieldrin, DD) in egg yolk to clarify their accumulation period and toxicity in chicken eggs. Laying hens were treated orally with a single dose of AD 1 mg/kg body weight. Concentrations (\(μ\)g/g) of AD or DD in the yolk of eggs laid for 21 days after AD treatment were determined by normal phase HPLC. The limits of determination were 0.02 \(μ\)g/g for AD and 0.03 \(μ\)g/g for DD, respectively. After AD treatment, although the low levels of AD (mean 0.02–0.03 \(μ\)g/g) were observed only during a three-day period (from 4th to 6th days), DD (mean 0.15 \(μ\)g/g) was found already on the 2nd day, indicating that the epoxidation of AD to DD in the hen’s body is rapid. The highest level of DD (mean 0.40 \(μ\)g/g) was detected on the 6th day, and then DD levels decreased slowly and were detected up to the 21st day. In this decreasing phase, the biological half-life of DD in the yolk was estimated to be 25.6 days. This study showed that in laying hens, AD, orally administrated, was rapidly metabolized to DD.